Community and health system factors associated with antiretroviral therapy initiation among men and women in Malawi: a mixed methods study exploring gender-specific barriers to care. Issue 3 (25th August 2020) - Phiri, Khumbo; McBride, Kaitlyn; Moucheraud, Corrina; Mphande, Misheck; Balakasi, Kelvin; Lungu, Eric; Kalande, Pericles; Hoffman, Risa M; Dovel, Kathryn
Abstract: Background: Although community and health system factors are known to be critical to timely antiretroviral therapy (ART) initiation, little is known about how they affect men and women. Methods: We examined community- and health system-level factors associated with ART initiation in Malawi and whether associations differ by gender; 312 ART initiates and 108 non-initiates completed a survey; a subset of 30 individuals completed an indepth interview. Quantitative data were analyzed using univariate and multivariate logistic regressions, with separate models by gender. Qualitative data were analyzed through constant comparison methods. Results: Among women, no community-level characteristics were associated with ART initiation in multivariable models; among men, receiving social support for HIV services (adjusted OR [AOR]=4.61; p<0.05) was associated with ART initiation. Two health system factors were associated with ART initiation among men and one for women: trust that accessing ART services would not lead to unwanted disclosure (women: AOR=4.51, p<0.01; men: AOR=1.71, p<0.01) and trust that clients were not turned away from ART services (men: 12.36, p=0.001). Conclusions: Qualitative data indicate that men were concerned about unwanted disclosure due to engaging in ART services and long waiting times for services. Interventions to remove health system barriers to ART services should be explored to promote social support among men.